Predictors and health-related quality of life with short form-36 for multidrug-resistant tuberculosis patients in Jambi, Indonesia: A case-control study - M. Dody Izhar; Marta Butar Butar; Fajrina Hidayati; Ruwayda Ruwayda (Elsevier, 2021)
Background: Multidrug-resistant tuberculosis (MDR-TB) is another problem in TB elimination. In 2018, 484,000 people worldwide developed tuberculosis that was resistant to rifampicin, and 78% of those had MDR-TB. Estimation of risk factors to detect MDR-TB. Methods: A case-control study assesses the estimate of the socio-demographic, house environment, diabetes mellitus, treatment behavior, and health-related quality of life (HRQOL). There were 28 cases of MDR-TB patients, and 56 control of drug-susceptible tuberculosis (DS-TB), in the treatment phase of October 1, 2019 to March 31, 2020. Results: The analysis showed a diabetes mellitus (adjusted odds ratio [AOR] 4.06, 95% confidence interval [CI] 1.31-12.54), treatment adherence (AOR 3.67, 95% CI 1.26-10.69), and supervisor of drugs swallowing (AOR 3.55, 95% CI 1.06-11.86) as a risk predictor for MDR-TB, and HRQOL independently associated with the incidence of MDR-TB (crude odds ratio [COR] 4.08, 95% CI 1.19-13.98), whereas socio-demographic and house environment was not a risk factor in this study. Validity and reliability of the SF-36 questionnaire (intraclass correlation coefficient [ICC], 0.658-0.802; Cronbach's α coefficient, 0.864). Conclusion: Diabetes mellitus, treatment adherence, supervisor of drugs swallowing as a risk predictor for MDR-TB. HRQOL of patients with MDR-TB was lower. The SF-36 questionnaire is valid and reliable to measure the HRQOL for TB/MDR-TB patients.